Claudicación En Equino Silla Argentina (2024)
Equine claudications are clinical manifestations of alterations in the structure and function of any of the limbs. These claudications show signs such as inflammation, pain or both. They are classified according to their degree, on a scale of 0 to 5 (Leon, 2011), and can be evaluated by means of a static or dynamic examination, complemented by taking radiographic plates, to observe the damage that may be present at the bone and joint level. Taking into account the above, internships were carried out in Carabineros de la Policía where a clinical case of Rosita was identified, a 17 year old mare, Argentine saddle breed, with the presence of relapsing claudication, clinical examination, diagnosis and appropriate treatment for the case will be performed.